Disentangling the Sources of Mimicry: Social Relations Analyses of the Link Between Mimicry and Liking. (January 2018) - Salazar Kämpf, Maike; Liebermann, Helén; Kerschreiter, Rudolf; Krause, Sascha; Nestler, Steffen; Schmukle, Stefan C.
Mimicry is an important interpersonal behavior for initiating and maintaining relationships. By observing the same participants ( N = 139) in multiple dyadic interactions (618 data points) in a round-robin design, we disentangled the extent to which mimicry is due to (a) the mimicker's general tendency to mimic (imitativity), (b) the mimickee's general tendency to evoke mimicry (imitatability), and (c) the unique dyadic relationship between the mimicker and the mimickee. We explored how these mimicry components affected liking and metaperceptions of liking (i.e., metaliking). Employing social relations models, we found substantial interindividual differences in imitativity, which predicted popularity. However, we found only small interindividual differences in imitatability. We found support for our proposition that mimicry is a substantially dyadic construct explained mostly by the unique relationship between two people. Finally, we explored the link between dyadic mimicry and liking, and we found that a person's initial liking of his or her interaction partner led to mimicry, which in turn increased the partner's liking of the mimicker.